Genetically Predicted Levels of Circulating Inflammatory Cytokines and the Risk and Age at Onset of Parkinson’s Disease: A Two-Sample Mendelian Randomization Study - Zhao, Yating; Zhang, Xiaoqian; Guo, Na; Tian, Dandan; Zhang, Chenguang; Mu, Changqing; Han, Chen; Zhu, Ruixia; Zhang, Jian; Liu, Xu (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) is widely considered to be a disabling neurodegenerative disorder which has been ranked second worldwide just after Alzheimer’s disease. Until now, a wide range of studies have focused on the role of circulating inflammatory cytokines in the development of PD. However, the causal relationship between circulating inflammatory cytokines and the risk and age at onset of PD has not been elucidated. Hence, to evaluate the effects of circulating inflammatory cytokines on the risk or age at onset of PD more accurately, we conducted this two-sample Mendelian randomization (MR) study involving summary statistics from genome-wide association studies (GWASs). Totally, we included a GWAS for inflammatory cytokines (8,293 participants), a meta-analysis of GWASs for PD risk (482,730 participants) and a GWAS dataset for age at onset of PD (17,996 PD patients). A total of 149 and 131 polymorphisms for exploring relationships between 19 inflammatory cytokines and the risk and age at onset of PD were obtained as instrumental variants. Then, we used a total of five MR methods including inverse-variance weighted, Wald ratio, MR Egger regression, weighted median and MR-pleiotropy residual sum and outlier (MR-PRESSO) method. Finally, we found a causal association between circulating levels of MIP1b and PD risk in IVW method (OR, 1.06; 95% CI, 1.02-1.10; P = 0.001). Meanwhile, other MR estimates by weighted median and MR-PRESSO method yielded similar effect estimates. Besides, we identified a suggestive association of IL-16 levels with PD risk (OR, 1.08; 95% CI, 1.00-1.17; P = 0.037). For age at PD onset, there was no evidence supporting its correlation with inflammatory cytokines. Our findings implied that MIP1b and IL-16 may be novel biomarkers and promising therapeutic targets for PD development.